EFFICACY OF NEEM SEED EXTRACT±ASHWAGANDHA FOR THE TREATMENT OF ENDOMETRITIS IN BUFFALOES - KADAM, P D; MARKANDEYA, N M; KUMAWAT, B L; SAWALE, A G; LAWANGE, S R; ANBHULE, R S (The Indian Journal of Animal Reproduction, 2022)
test of cervico-vaginal mucus (CVM) and endometrial cytology were divided equally into three groups. Group-Icontaining fresh endometritic buffaloes (repeated ≤7 times) was administered once with Methanolic Neem seedextract (100 mcg/ml) @ 30 ml by intrauterine (IU) route, Group-II consisting of chronic endometritic buffaloes(repeated >7 times) was administered with Methanolic Neem seed extract (100 mcg/ml) @ 30 ml IU once onlyplus 15 gm Ashwagandha powder by oral route for 5 days and Group-III as a control group was administered withplacebo as 30 ml PBS through IU. In both treated groups, pH of CVM deceased (p
Keywords: Ashwagandha; Buffaloes; Efficacy; Endometritis; Methanolic Neem seed extract